Analysis Of Cadmium (Cd) And Lead (Pb) Levels In Water Samples By Atomic Absorption Spectrophotometry (AAS) At The Lampung Health Laboratory Center - Calesta Adinda; Elly Lestari Rustiati; Iproh Susanti; Okferina Cicilia (Ann Publisher, 2026)
Background. For sanitary hygiene, water is used for maintaining personal hygiene, such as bathing and brushing, as well as for food washing, dishwashing, and laundry in daily life, so its quality differs from that of drinking water. This study focuses on heavy metal pollution, particularly lead (Pb) and cadmium (Cd), which are known toxic substances harmful to living organisms. Aims. Its purpose is to determine the levels of cadmium and lead in water samples by atomic absorption spectrophotometry at the Lampung Health Laboratory Center, conducted in December 2024-January 2025. T Methods. The method refers to SNI No. 6989.84 of 2019 for 78 samples of sanitary hygiene water by Atomic Absorption Spectrophotometry (SSA). Cadmium (Cd) analysis of 37 samples: 21 were positive for Cd, but none exceeded the threshold limit value of 0.003 mg/L. Conclusion. Meanwhile, the results of the lead (Pb) analysis showed that 1 of 37 samples did not exceed the threshold limit value of 0.01 mg/L, as stipulated in the Indonesian Minister of Health Regulation No. 2 of 2023.